TI_GERICHTE 12.2003.190 vom 3. Februar 2005 , compravendita immobiliare - garanzia per difetti - promesse del mediatore - TI Tribunale d'appello (2005)
compravendita immobiliare - garanzia per difetti - promesse del mediatore